Teaching Residents Chest Tubes: Simulation Task Trainer or Cadaver Model? - Ting Xu Tan; Paula Buchanan; Erin Quattromani (Emergency Medicine International)
Objective. To compare simulation task trainers (sim) with cadaver for teaching chest tube insertion to junior residents. Methods. Prospective study involving postgraduate year (PGY) one and two emergency medicine (EM) and PGY-1 surgery residents. Residents were randomized into sim or cadaver groups based on prior experience and trained using deliberate practice. Primary outcomes were confidence in placing a chest tube and ability to place a chest tube in a clinical setting during a seven-month follow-up period. Secondary outcomes include skill retention, using an objective assessment checklist of 15 critical steps in chest tube placement, and confidence after seven months. Results. Sixteen residents were randomized to cadaver (n=8) and simulation (n=8) groups. Both groups posttraining had statistically significant increase in confidence. No significant difference existed between groups for median posttraining assessment scores (13.5 sim v 15 cadaver). There was no statistically significant difference between groups for confidence at any point measured. There was moderate correlation (0.58) between number of clinical attempts reported in a seven-month follow-up period and final assessment score. Conclusion. Both sim and cadaver models are effective modalities for teaching chest tube placement. Medical education programs can use either modalities to train learners without notable differences in confidence.